Pengaruh Pendidikan Kesehatan Video Animasi Terhadap Perilaku Ibu Nifas Primipara Dalam Perawatan Bayi - Prihandina, Fatika Nurindah; Winarni, Sri; Setyarini, Didien Ika; Yulifah, Rita (Program Studi DIV Kebidanan Fakultas Ilmu Kesehatan Universitas Muhammadiyah Gorontalo, 2025)
During the transition from intrauterine to extrauterine life, newborns require support to meet their needs for stimulation and play (ASAH), affection and emotional support (ASIH), as well as physical care, nutrition, and hygiene (ASUH). Mothers, as the closest caregivers, are expected to provide daily newborn care. This study aimed to analyze the effect of health education using animated video media on the behavior of primiparous postpartum mothers in caring for their babies, including bathing, umbilical cord care, and breastfeeding. The study employed a one-group pretest–posttest design with a Research and Development (R&D) approach. The population consisted of 15 primiparous postpartum mothers in June–July 2024, selected through total sampling. Instruments included a demographic questionnaire and a self-assessment checklist on newborn care practices. The intervention was delivered through animated video media accompanied by a brief demonstration by the researcher to clarify parts that mothers did not fully understand. Data were analyzed using the Wilcoxon Signed Rank Test, which showed a significant difference (p = 0.001). The results demonstrate that animated video education supplemented with a brief demonstration effectively improved maternal newborn care behavior. In conclusion, health education combining animated video and brief demonstration significantly enhances the ability of primiparous postpartum mothers to perform daily newborn care.